الخصائص الميكانيكية للبيتون الخفيف المسلح بالألياف الفولاذية - أصلان, طارق; ناصر, عصام; الجبيلي, نسرين (Latakia University Journal -Engineering Sciences Series, 2017)
يتناول هذا البحث دراسة الخصائص الميكانيكية للبيتون الخفيف المسلح بالألياف الفولاذية. وقدتم الحصول على البيتون الخفيف باستخدام حصويات السكوريا المتوفرة بكميات كبيرة في الجمهورية العربية السورية. صممت ثلاث خلطات بيتونية بنسب مختلفة من الألياف الفولاذية 0.75)% , 0.5,0)(على أساس حجمي). تم إجراء مجموعة من الاختبارات على عينات اسطوانية وموشورية مأخوذة من هذه الخلطات لتعيين الخصائص الميكانيكية للبيتون الناتج والمتمثلة بالمقاومة على الضغط، معامل المرونة، الشد بالانفلاق، والشد بالانعطاف كما تم إيجاد سلوك البيتون (العلاقة إجهاد-تشوه) تحت تأثير الضغط. بيّنت النتائج ازدياد قيم مقاومة الضغط ومقاومة الشد بالانفلاق ومقاومة الانعطاف بنسب تصل لـ16.9%و25.6% و 53.6%عند استخدام الألياف الفولاذية على الترتيب. كما أظهرت أهمية استخدام الألياف الفولاذية لتحسين أداء البيتون وتحويل سلوكه الهش إلى سلوك مطاوع.Thepaper studies the mechanical properties ofsteel fibers reinforced lightweight concrete.This kind of concrete is produced by usingscoria aggregateswhich can be found abundantly in Syria. Thelightweight concrete mixeswere designed for three different percentage of steel fibers (0, 0.5, 0.75)%.Different tests were performed to determine mechanical properties of product concrete such as compressive strength, elasticity modulus, splitting tensile strengthand flexural strengthalso; the stress–strain diagram of produced lightweight concrete was established under compression. The results showedanincrease of the compressive, splitting tensile and flexural strengths reach up 16.9%, 25.6%, and 53.6% respectivelywhen the steel fibers were used. Also the results indicated the importance of using the steel fibers to improve the performance of concrete and change its brittle behavior to ductile behavior.